Cardiovascular Risk in Pediatrics: A Dynamic Process during the First 1000 Days of Life - Valeria Calcaterra; Savina Mannarino; Vittoria Garella; Virginia Rossi; Elia Mario Biganzoli; Gianvincenzo Zuccotti (MDPI AG, 2023)
The early childhood period, encompassing prenatal and early stages, assumes a pivotal role in shaping cardiovascular risk factors. We conducted a narrative review, presenting a non-systematic summation and analysis of the available literature, focusing on cardiovascular risk from prenatal development to the first 1000 days of life. Elements such as maternal health, genetic predisposition, inadequate fetal nutrition, and rapid postnatal growth contribute to this risk. Specifically, maternal obesity and antibiotic use during pregnancy can influence transgenerational risk factors. Conditions at birth, such as fetal growth restriction and low birth weight, set the stage for potential cardiovascular challenges. To consider cardiovascular risk in early childhood as a dynamic process is useful when adopting a personalized prevention for future healthcare and providing recommendations for management throughout their journey from infancy to early adulthood. A comprehensive approach is paramount in addressing early childhood cardiovascular risks. By targeting critical periods and implementing preventive strategies, healthcare professionals and policymakers can pave the way for improved cardiovascular outcomes. Investing in children's health during their early years holds the key to alleviating the burden of cardiovascular diseases for future generations.